Evaluation Of User Experience In Purchasing Watches On The Watch Studio Website Using The User Experience Questionnaire Method - Alamsyah, Puji Rahma; Kholil, Ishak (Sean Institute, 2025)
This Based on observations of the Watch Studio website for purchasing watches, there are still both positive and negative complaints from users of the Watch Studio website. A lack of product information and the absence of feedback on the Watch Studio website result in users obtaining very limited information. The purpose of this study is to measure the level of user experience with the services provided by the Watch Studio website. The research method employs quantitative data through observations of the Watch Studio website and distributing questionnaires that include several questions related to the topic, with responses scored on a scale of 1 to 7. The results are then analyzed using the User Experience Questionnaire (UEQ) method. A questionnaire is a data collection technique that involves providing several questions in the form of links or written forms to respondents for them to answer. The results of the study conducted by the author on the Watch Studio website can be summarized as follows: this study successfully evaluated the user experience on the Watch Studio website for each aspect of the User Experience Questionnaire (UEQ). From the research findings, it can be concluded that the accuracy scale on the Watch Studio website indicates the need to clearly and comprehensively describe the products, provide photos or other information sufficient for users to make purchases, and ensure that the customer service team responds quickly so users feel supported during the purchasing process. To achieve better research outcomes, active participation from respondents in providing feedback is essential for the development of an improved system.